Analysis and Improvement Design on P2P Botnets Detection Framework - Raihana Syahirah Abdullah, RS Abdullah; Mohd Faizal Abdollah, Faizal M.A.; Zul Azri Muhamad Noh, ZAM Noh (Praise Worthy Prize, 2013)
Developing the P2P botnets detection framework is crucial when we trying to fight against P2P botnets. Poor detection method can lead to a failure of P2P botnets detection. Thus, it needs to be accurately functioned well. This paper reviews and evaluates various current frameworks of P2P botnets detection and analyzing the existing gaps to make improvement of P2P botnets detection framework. Based on a review that conducted manually, we report our findings and analysis has been done on different frameworks concern on P2P botnets detection. Consequently, the gap and motivations found from this reviews are discussed. Then, the P2P botnets detection framework architecture has been proposed with the new improvement been reinforced by hybrid detection technique, hybrid analyzer and in-depth hybrid analysis. Future directions of this review are to develop the P2P botnets detection system that has capability in high detection accuracy and efficiency.